Total edge irregularity strength of some cycle related graphs - Ramalakshmi Rajendran; Kathiresan KM (Indonesian Combinatorial Society (InaCombS), 2021)
An edge irregular total k-labeling f : V ∪ E → 1,2, ..., k of a graph G = (V,E) is a labeling of vertices and edges of G in such a way that for any two different edges uv and u'v', their weights f(u)+f(uv)+f(v) and f(u')+f(u'v')+f(v') are distinct. The total edge irregularity strength tes(G) is defined as the minimum k for which the graph G has an edge irregular total k-labeling. In this paper, we determine the total edge irregularity strength of new classes of graphs Cm @ Cn, Pm,n* and Cm,n* and hence we extend the validity of the conjecture tes(G) = max ⌈|E(G)|+2)/3⌉, ⌈(Δ(G)+1)/2⌉ for some more graphs.